Биология атомного века: (проблемы радиобиологии) : [сборник] (Новое в жизни, науке, технике, 1983)
Экземпляры: КХ (20120927) / Инвентарный номер: 0262192 / Цена: 0.11 / Сис.шифр: 577.1 / Авт.знак: Б 63 / ГРНТИ: 34 / ББК: 28